(untitled) (Proceedings of International Conference on Modern Science and Scientific Studies, 2024)
This article explores the fascinating realm of electromagnetic waves, shedding light on their fundamental characteristics, properties, and applications. The study investigates the various types of electromagnetic waves, their behavior, and the crucial role they play in the modern world. Through a detailed literature analysis, this article aims to enhance our understanding of these waves, covering essential concepts, methods, and recent advancements. The results section highlights key findings, leading to a comprehensive discussion on the implications and potential future directions in the field of electromagnetic waves.